Copular Constructions and Their Role in Meaning Negotiation in Trending Online Political Discussions - Mauti, Alyanah B.; Sieras, Shangrela G. (International Journal of Language and Literary Studies, 2026)
Copular constructions are central to expressing evaluation, identity, and relational meaning. In online political discussions, especially on social media, these structures help users negotiate stances and frame opinions as facts. This study examines the frequency and roles of copular constructions in online political discussions, focusing on three Reddit posts about the Anti-Political Dynasty Bill in the Philippines. Using Higgins’ (1979) typology and Halliday’s Systemic Functional Linguistics (SFL), the research analyzed seventy-three copular constructions extracted from Reddit. The findings show a high frequency of copular constructions, especially in argumentative and evaluative comments. Ascriptive constructions are the most common, followed by equative and locative forms. The analysis reveals that these constructions serve more than grammatical functions; they are important tools for negotiating meaning. Ascriptive forms let users present personal evaluations as inherent traits of political figures. Equative forms frame interpretations as authoritative definitions, while locative forms tie abstract arguments to real procedural or spatial contexts. The study concludes that copular structures are essential for expressing ideologies in digital civic spaces. It suggests shifting toward a functional-discourse approach in English Language Teaching (ELT) in the Philippines, highlighting how relational processes can help develop critical language awareness and argumentative skills among Filipino learners.